PREVALENCE OF CHRONIC GASTRITIS AMONG STUDENTS - Мовлонов А. А.; Жалолов Н. Н. (The Conference Hub, 2025)
This article discusses the prevalence of chronic gastritis among students, as well as the main causes that contribute to its development. Risk factors such as an unbalanced diet, fast food, irregular diet, stress and bad habits are analyzed. The data of scientific research and statistical information on morbidity among students from different countries are given. The article also discusses possible preventive measures aimed at reducing the incidence of chronic gastritis among young people.
Keywords: chronic gastritis, students, prevalence, nutrition, fast food, stress, gastrointestinal diseases, prevention.